Implementasi Asas Keseimbangan Bagi Para Pihak dalam Perjanjian Baku - Aryo Dwi Prasnowo; Siti Malikhatun Badriyah (University of Udayana, 2019)
Businessman are required to increase the efficiency of transaction time in serving consumers, therefore a practical agreement is made and the contents have been determined by one party so that the other party does not have the opportunity to negotiate and is in the position of